Cardiovascular Complications During Delivery Hospitalization in Patients With Psoriasis - Ankit Agrawal, MD; Sharmeen Sorathia, MD; Umesh Bhagat, MD; Salman Zahid, MD; Aro Daniela Arockiam, MD; Aqieda Bayat, MD; Ahmad Safdar, MD; Akiva Rosenzveig, MD; Muhammad Majid, MD; Sanya Chandna, MD; Rahul Gupta, MD; Brittany Weber, MD, PhD; et al. (JACC: Advances)
Background: Psoriasis in pregnancy is associated with adverse maternal outcomes. However, there are limited data on this subject. Objectives: The purpose of our study was to investigate the association between psoriasis and related cardiovascular complications during delivery. Methods: The National Inpatient Sample was used to identify hospitalizations for delivery from 2011 to 2020. Propensity score matching was performed to study the association of psoriasis with the primary outcomes of in-hospital medical and obstetric complications. Results: A total of 37,482,206 weighted delivery hospitalizations in women ≥18 years were identified; of which, 23,588 patients had psoriasis. Pregnant patients with psoriasis had a higher incidence of complications during delivery, including preeclampsia/eclampsia, acute kidney injury, pulmonary edema, cardiac arrhythmias, and venous thromboembolism compared to those without psoriasis. In propensity-matched analysis, psoriasis was significantly associated with a higher risk of preeclampsia/eclampsia (OR: 1.25, 95% CI: 1.08 to 1.43, P = 0.002) and cardiac arrhythmias (OR: 1.44, 95% CI: 1.08-1.93, P = 0.012), compared to patients without psoriasis. Conclusions: Delivery hospitalizations in patients with psoriasis are associated with a higher risk of preeclampsia/eclampsia and cardiac arrhythmias.